Association of social-environmental factors with cognitive function in children with sickle cell disease. Issue 3 (3rd April 2017) - Yarboi, Janet; Compas, Bruce E.; Brody, Gene H.; White, Desiree; Rees Patterson, Jenny; Ziara, Kristen; King, Allison
ABSTRACT: The aim of this study was to examine the relationship between cognitive function in pediatric sickle cell disease (SCD) patients and mothers' reports of social-environmental stress, depressive symptoms, and parenting. A total of 65 children with SCD completed comprehensive neuropsychological testing to assess several domains of cognitive functioning, including general intellectual ability, academic achievement, and executive function. Mothers reported on demographics, social-environmental stress, depressive symptoms, and parenting. As predicted, children with SCD significantly underperformed relative to normative data on measures of cognitive function. Associations between maternal social-environmental stress, maternal depressive symptoms, and parenting were mixed. The results show partial support for the hypothesis that greater stress and depressive symptoms and less positive parenting are associated with poorer cognitive function in children with SCD. Linear regression analyses showed that maternal financial stress was the strongest predictor across all domains of cognitive function. The findings replicate and extend past research, reaffirming that children with SCD are at risk for cognitive impairment across multiple domains. Additionally, social-environmental stress, particularly financial strain, is linked to mothers' depressive symptoms and parenting behaviors as well as children's cognitive function. Future studies using direct observations of parenting behaviors are needed. These findings, along with recent research on parenting interventions, may inform the development of concrete, teachable parenting and coping skills to improve cognitive functioning in children with SCD.